THE ROLE AND CONTRIBUTION OF BALAI BENIH IKAN (BBI) RAMBUNG MERAH TOWARDS DEVELOPMENT OF AQUACULTURE AT SIMALUNGUN DISTRICT OF NORTH SUMATERA PROVINCE - Frischa Sonawaty Theresia Sianturi; Lamun Bathara; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on December 2015 at Balai Benih Ikan (BBI) Rambung Merah Simalungun District of North Sumatera Province. This research purposed were : 1) To identify the role of BBI Rambung Merah in the development of aquaculture 2) To identify function of BBI Rambung Merah in the development of aquaculture 3) To know the contribution of BBI Rambung Merah in suplying the seed of fish. The Method used for this research was survey method, with 15 respondents. There are head of BBI Rambung Merah, technician of BBI Rambung Merah and farmers of fish.The results indicated that BBI Rambung Merah will work when carrying out the role and function well. The role that is run and should be maintained such as : Science and technology center of aquaculture, the training and extension center of fisheries, provider seed of fresh water fish, the connector between the goverment and farmers of fish. Mean while, the function that should be run and must be mantained such as : the implementation control and coordination of the production and distribution, the implementation of the guidance operational and the production technicial of the fish seed, the increasing and keeping of the quantity and quality of fresh water fish seed, the administrative management of BBI Rambung Merah, the application of conservation resources of fish and techniques to control pests and diseases, to do a partnership and to control the activity of UPR. In addition BBI Rambung Merah has given contribution to Simalungun District about supply of fish, though it is low.Keyword : Role, Function, Contribution, Fish Breeding, Rambung Merah